NLRP3 inflammasome in NMDA-induced retinal excitotoxicity. (April 2019) - Tsoka, Pavlina; Barbisan, Paulo R.; Kataoka, Keiko; Chen, Xiaohong Nancy; Tian, Bo; Bouzika, Peggy; Miller, Joan W.; Paschalis, Eleftherios I.; Vavvas, Demetrios G.
Abstract : N-methyl-D-aspartate (NMDA)-induced excitotoxicity is an acute form of experimental retinal injury as a result of overactivation of glutamate receptors. NLRP3 (nucleotide-binding domain, leucine-rich-repeat containing family, pyrin domain containing-3) inflammasome, one of the most studied sensors of innate immunity, has been reported to play a critical role in retinal neurodegeneration with controversial implications regarding neuroprotection and cell death. Thus far, it has not been elucidated whether NMDA-mediated excitotoxicity can trigger NLRP3 inflammasome in vivo . Moreover, it is unknown if NLRP3 is beneficial or detrimental to NMDA-mediated retinal cell death. Here, we employed a murine model of NMDA-induced retinal excitotoxicity by administering 100 nmoles of NMDA intravitreally, which resulted in massive TUNEL + (TdT-dUTP terminal nick-end labelling) cell death in all retinal layers and especially in retinal ganglion cells (RGCs) 24 h post injection. NMDA insult in the retina potentiates macrophage/microglia cell infiltration, primes the NLRP3 inflammasome in a transcription-dependent manner and induces the expression of interleukin-1β (IL-1β). However, despite NLRP3 inflammasome upregulation, systemic deletion of Nlrp3 or Casp1 (caspase-1) did not significantly alter the NMDA-induced, excitotoxicity-mediated TUNEL + retinal cell death at 24 h (acute phase). Similarly, the deletion of the two aforementioned genes did not alter the survival of the Brn3a + (brain-specific homeobox/POU domain protein 3A) RGCs in a significant way at 3- or 7-days post injection (long-term phase). Our results indicate that NMDA-mediated retinal excitotoxicity induces immune cell recruitment and NLRP3 inflammasome activity even though inflammasome-mediated neuroinflammation is not a leading contributing factor to cell death in this type of retinal injury. Highlights: NMDA excitotoxicity induces immune cell infiltration in the retina. NMDA retinal excitotoxicity triggers NLRP3 inflammasome priming. Nlrp3−/− or Casp1−/− do not have major impact on overall neuronal loss after NDMA.